Stunting - Hanswanti Putri Niasti Nauli Lase; Inda M. H. Sinaga (Jurnal Kedokteran Methodist, 2025)
Background: Stunting, or failure to thrive, is a chronic nutritionalcondition resulting from prolonged inadequate nutrient intake. In the shortterm, stunting can increase morbidity; in the long term, it manifests asdelayed bone growth and low body weight. Children with stunting aresignificantly shorter than their peers. Objective: This study aims to identifythe multifaceted risk factors contributing to stunting. Discussion: Stuntingis influenced by a complex interplay of environmental and genetic factors.Key environmental determinants include maternal nutritional status, childfeeding patterns, and environmental sanitation. While hereditary factorsand hormonal imbalances play a role, malnutrition remains a primarypreventable cause of short stature in children. Conclusion: Understandingboth environmental and genetic factors is crucial for the effectiveprevention of stunting and the improvement of children's nutritionalhealth.